2020
DOI: 10.1093/infdis/jiaa104
|View full text |Cite
|
Sign up to set email alerts
|

Low Neuroactive Steroids Identifies a Biological Subtype of Depression in Adults with Human Immunodeficiency Virus on Suppressive Antiretroviral Therapy

Abstract: Background The prevalence and mortality risk of depression in people with human immunodeficiency virus (HIV) infection receiving antiretroviral therapy (ART) is higher than in the general population, yet biomarkers for therapeutic targeting are unknown. In the current study, we aimed to identify plasma metabolites associated with depressive symptoms in people with HIV receiving ART. Methods This is a prospective study of ART-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In our study, we observed increased plasma glutamate in both the cohorts and low neuroactive steroids in PLWH with therapy compared to the HC. A recent study in PLWH with high and low depressive symptoms also reported a reduced level of neuroactive steroids in participants with high depressive symptoms (28) indicating that depression severity associate with lower levels of neuroactive steroids. Interestingly, neuroactive steroids have been shown to regulate glutamatergic neurotransmission (can bind to receptors for glutamate) as well as behavioral actions (29).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our study, we observed increased plasma glutamate in both the cohorts and low neuroactive steroids in PLWH with therapy compared to the HC. A recent study in PLWH with high and low depressive symptoms also reported a reduced level of neuroactive steroids in participants with high depressive symptoms (28) indicating that depression severity associate with lower levels of neuroactive steroids. Interestingly, neuroactive steroids have been shown to regulate glutamatergic neurotransmission (can bind to receptors for glutamate) as well as behavioral actions (29).…”
Section: Discussionmentioning
confidence: 89%
“…In conclusion, our present study based on cohorts (India and Cameroon) indicated altered AA metabolism and more potentially a switch in glutaminolysis as the alternative pathway for energy production following a long-term antiretroviral therapy, corroborating our earlier study (3). Altered glutaminolysis with long-term treatment and its association with metabolic syndrome (3), diminished immune recovery (4), and glutamate excitotoxicity mediated neuro-cognitive impairments can lead to increased co-morbidities and accelerated aging in PLWH with successful therapy.In addition, a decrease in neurosteroids causes major depressive syndrome (28) leading to diminished quality of life despite successful treatment. Our study also provided evidence displaying the cross-talk between glutaminolysis, TCA cycle and OXPHOS in HIV-latent cell model being more specific to promonocytic U1 cells that potentially is linked with apoptosis as well as latency reversal.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed increased plasma glutamate in both the cohorts and low neuroactive steroids in PLWH with therapy compared to the HC. A recent study in PLWH with high and low depressive symptoms also reported a reduced level of neuroactive steroids in participants with high depressive symptoms 28 indicating that depression severity associated with lower levels of neuroactive steroids. Interestingly, neuroactive steroids have been shown to regulate glutamatergic neurotransmission (can bind to receptors for glutamate) as well as behavioral actions 29 .…”
Section: Discussionmentioning
confidence: 90%
“…Altered glutaminolysis with long-term treatment and its association with metabolic syndrome 3 , diminished immune recovery 4 , and glutamate excitotoxicity mediated neurocognitive impairments can lead to increased co-morbidities and accelerated aging in PLWH with successful therapy. In addition, a decrease in neurosteroids causes major depressive syndrome 28 leading to diminished quality of life despite successful treatment. Our study also provided evidence displaying the cross-talk between glutaminolysis, TCA cycle, and OXPHOS in HIV-latent cell model being more specific to promonocytic U1 cells that potentially is linked with apoptosis as well as latency reversal.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that a substantial number of patients was not receiving cART, while some cART receiving subjects were using antiretroviral drugs with known psychiatric side effects, and significant mitochondrial toxicity, which might have interfered with acylcarnitine alterations [ 23 ]. A second study in two cohorts of 55 and 44 PLWH identified lower steroids to be associated with depression [ 24 ]. In this study, patients with mild symptoms were excluded, thus ignoring a major part of the depression continuum.…”
Section: Introductionmentioning
confidence: 99%